Research progress of black tea thearubigins: a review - Zhu, Kun; Ouyang, Jie; Huang, Jianan; Liu, Zhonghua (Critical reviews in food science and nutrition, 2021)
As the most abundant component in black tea, thearubigins (TRs) contribute a lot to black tea's characteristic color, mouthfeel, and potential health benefits. But compared to lower molecular weight black tea polyphenols, there are fewer researches that focus on TRs because of their heterogeneity. This review summarized recent research progress on (1) isolation method of TRs; (2) structure analysis and formation mechanism of TRs; (3) biofunctions of TRs, including antioxidation, antimutagenic and anticancer effects, effects on mitochondrial activation, gastrointestinal motility and skeletal health, to show some future research aspects and prospects of TRs.